Evaluating the Quality of Life among Menopausal Women in the Urban Field Practice Area of a Medical College in Guntur - Muhseenah; Samson Sanjeeva Rao Nallapu (Journal of Mid-Life Health)
Background: Coping with menopause is always a troublesome issue in every woman’s life. Most women, at the time of permanent cessation of menstruation, experience various symptoms due to hormonal fluctuations which may affect their quality of life (QOL) leading to anxiety and concern. This study is set to study the QOL among menopausal women in an urban low socioeconomic area of Guntur city. Methodology: A descriptive cross-sectional study was conducted involving menopausal women between the ages of 40 and 60 years living in the urban field practice area of the Department of Community Medicine, NRI Medical College, using a predesigned semistructured schedule covering sociodemographic and QOL-related aspects. Results: The study included 400 menopausal women with mean age of 51.98 ± 6.40. Most of the women were from the lower socioeconomic stratum. Two hundred and thirty-six (59%) women attained menopause naturally, whereas 164 (41%) had induced menopause. The mean age of attainment of menopause was 40.03 ± 8.32. The mean score for the physical domain of the QOL was 32.05 ± 11.73 (limits 15–75), the psychological domain of the QOL was 33.11 ± 13.33 (limits 14–70), and the social and environmental domain was 17.52 ± 5.89 (limits 10–50). Age above 50 years, poor educational levels, lower socioeconomic status, longer duration since menopause, poor awareness of menopausal symptoms, and comorbidities were significantly associated with overall QOL. Conclusion: Women need sufficient knowledge and awareness about the symptoms of menopause. Menopausal women must be made aware that what they are going through is common to other women too and that medical help is available. The family and community must also be sufficiently sensitized to their healthcare needs.